Pendidikan Karakter Melalui Buku Teks Bahasa Arab di Pesantren Modern Cirebon (Studi Kasus di Pondok Pesantren Modern Al-Muqoddas) - Pradi Khusufi Syamsu; Abdul Gafur Arifin (At-Ta'dib, 2025)
Purpose - This study investigates the implementation of character education in Arabic language instruction at Al-Muqoddas Modern Pesantren in Cirebon through the use of the al-Qira’ah ar-Rashidah textbook. Rooted in the growing discourse on the integration of moral values within language learning, this research aims to analyze how Arabic learning can serve as an effective medium for character building in Islamic boarding school contexts. Methods -Employing a qualitative approach, data were collected through observation, interviews, and documentation, and analyzed using triangulation to ensure data validity and credibility. Findings –The findings reveal that the character values embedded in the al-Qira’ah ar-Rashidah textbook authored by Abdul Fatah Shabri and Ali Umar and published by Dar al-Ma'arif, Egypt not only align with but also exceed the character education standards established by Indonesia’s Ministry of National Education. The implementation of character education in Al-Muqoddas is integrated across various learning strategies, including expository, inquiry-based, contextual, and problem-based approaches. Furthermore, character internalization is reinforced through practical strategies such as modeling, habituation, experiential learning, direct advice, and disciplinary measures. Research implications suggest that Arabic language instruction, when enriched with cultural and moral content, offers a robust framework for instilling Islamic character values. However, this study is limited to one pesantren context and may not represent all Islamic educational settings. Originality/value of this research lies in its contextual exploration of how classical Arabic learning materials can effectively serve dual functions—linguistic proficiency and character development within a pesantren framework, reinforcing the inseparability of language and moral education in Islamic pedagogy.